Evidence on the Financial Sector of Hang Seng Index from Hong Kong Stock Market’s Reaction to Dividend Announcement - Zhao, Yi (2009)
This paper mainly discusses problems of the relationship between dividend announcement and stock market and preannouncement information leakage through the data in Hang Seng Index. The histories of Hong Kong Stock Market and Hang Seng Index are illustrated to help readers get to be familiar with the stock market. A relative number of literatures have been utilized to take a further look at the problem of “stock market reaction to dividend announcement”, through variety countries or prospects. In order to find whether there is any evidence on the fact the dividend announcement has the impact on the returns in Hong Kong Stock Exchange, we use a sample of 13 companies from Financial Sector of Hang Seng Index with the method of event study and the study period is January 2005 to December 2008. The conventional market model is applied. In this paper, there are two measurements have been calculated to approach the result. And t-test is used to test the statistical significance. The results of the paper represent the dividend announcements have impact on the Hong Kong Stock Exchange significantly. However, information leakage is not evident before the dividend announcement in the stock market. The findings also give an explanation for that dividend announcement carries some significant information content. What’s more, the Hong Kong Stock Market is a semi-strong form. The investors gain value after the dividend announcement and the return of the companies is increasing from the dividend release day. Overall, the results could be supported by the previous literatures.